Medical Therapy for Systemic Right Ventricles: A Systematic Review (Part 1) for the 2018 AHA/ACC Guideline for the Management of Adults With Congenital Heart Disease. Issue 14 (2nd April 2019) - Zaragoza-Macias, Elisa; Zaidi, Ali N.; Dendukuri, Nandini; Marelli, Ariane
Abstract : Patients with systemic morphological right ventricles (RVs), including congenitally corrected transposition of the great arteries and dextro-transposition of the great arteries with a Mustard or Senning atrial baffle repair, have a high likelihood of developing systemic ventricular dysfunction. Unfortunately, there are a limited number of clinical studies on the efficacy of medical therapy for systemic RV dysfunction. We performed a systematic review and meta-analysis to assess the effect of angiotensin-converting enzyme (ACE) inhibitors, angiotensin-receptor blockers (ARBs), beta blockers, and aldosterone antagonists in adults with systemic RVs. The inclusion criteria included age ≥18 years, systemic RVs, and at least 3 months of treatment with ACE inhibitor, ARB, beta blocker, or aldosterone antagonist. The outcomes included RV end-diastolic and end-systolic dimensions, RV ejection fraction, functional class, and exercise capacity. EMBASE, PubMed, and Cochrane databases were searched. The selected data were pooled and analyzed with the DerSimonian-Laird random-effects meta-analysis model. Between-study heterogeneity was assessed with Cochran's Q test. A Bayesian meta-analysis model was also used in the event that heterogeneity was low. Bias assessment was performed with the Newcastle-Ottawa Scale and Cochrane Risk of Bias Tool, and statistical risk of bias was assessed with Begg and Mazumdar's test and Egger's test. Six studies met the inclusion criteria, contributing a total of 187 patients; treatment with beta blocker was the intervention that could not be analyzed because of the small number of patients and diversity of outcomes reported. After at least 3 months of treatment with ACE inhibitors, ARBs, or aldosterone antagonists, there was no statistically significant change in mean ejection fraction, ventricular dimensions, or peak ventilatory equivalent of oxygen. The methodological quality of the majority of included studies was low, mainly because of a lack of a randomized and controlled design, small sample size, and incomplete follow-up. In conclusion, pooled results across the limited available studies did not provide conclusive evidence with regard to a beneficial effect of medical therapy in adults with systemic RV dysfunction. Randomized controlled trials or comparative-effectiveness studies that are sufficiently powered to demonstrate effect are needed to elucidate the efficacy of ACE inhibitors, ARBs, beta blockers, and aldosterone antagonists in patients with systemic RVs. Abstract : Supplemental Digital Content is available in the text.